(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
The digital revolution, encompassing the global economy, astonishes with its scale, pace, and geography. Each year, the intensity of introducing new technologies into production and services designed to meet human needs increases. The digital wave is affecting new sectors and is having an increasingly significant impact on the economy. The article discusses the key features of digital transformation using inspections as an example. Additionally, it highlights the primary factors accelerating the digitization processes in our republic.